2006
DOI: 10.1002/kin.20159
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of substituent effects of 2‐substituted alkyl ethyl methylcarbonates in homogeneous, unimolecular gas phase elimination kinetics

Abstract: Theoretical studies on the gas phase elimination of 2-substituted alkyl ethyl methylcarbonates were performed at the B3LYP/6-31G * and B3LYP/6-31+G * * level of theory. The results of these calculations provide additional evidence that the mechanism of carbonates with a C β H bond proceeds through a concerted nonsynchronous six-membered cyclic transition state to produce methylcarbonic acid and the corresponding olefin. The unstable intermediate, methylcarbonic acid, rapidly decomposes through a four-membered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The dominance of the two-step decomposition in DEC unimolecular decomposition has already been addressed in previous studies [24,25]. In the present work, the pressure and temperature dependent rate coefficients for DEC dissociations were theoretically determined for the first time.…”
Section: Dec Pyrolysis In a Flow Reactormentioning
confidence: 59%
See 1 more Smart Citation
“…The dominance of the two-step decomposition in DEC unimolecular decomposition has already been addressed in previous studies [24,25]. In the present work, the pressure and temperature dependent rate coefficients for DEC dissociations were theoretically determined for the first time.…”
Section: Dec Pyrolysis In a Flow Reactormentioning
confidence: 59%
“…Previous studies [24,25] have suggested that an intra-molecular hydrogen transfer [DEC → C 2 H 5 C(=O)OH+C 2 H 4 ] is the predominant pathway for DEC unimolecular decomposition. In the previous model [3] the rate coefficient of this important reaction was assigned with the extrapolation of an earlier measurement [26] without considering the pressure-dependence.…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…26 The results of these calculations provide additional evidence that the mechanism for carbonates with a C β -H bond proceeds through a concerted non-synchronous six-membered cyclic transition state to produce methylcarbonic acid and the corresponding alkene. The unstable intermediate, methylcarbonic acid, rapidly decomposes through a four-membered cyclic transition state to methanol and carbon dioxide.…”
Section: Acid Derivativesmentioning
confidence: 65%
“…The fastest reaction is for Z = NCCH 2 CH 2 , suggesting that the acidity of the β‐hydrogen is not a factor for this series of compounds. Entropies of activation suggest a loose TS structure, compared to other types of elimination reactions 16,17. The TS is late in the reaction coordinate in the sense of CBr bond breaking, being more advanced for Z = NCCH 2 CH 2 .…”
Section: Discussionmentioning
confidence: 92%
“…Theoretical calculations have proved useful in the investigation of the reaction mechanism in a number of reactions 15–17. Particularly, gas‐phase reactions are interesting because of the absence of solvent effects.…”
Section: Introductionmentioning
confidence: 99%